Quantitative Analysis of Situation Awareness (QASA): modelling and measuring situation awareness using signal detection theory. Issue 6 (3rd June 2018) - Edgar, Graham K.; Catherwood, Di; Baker, Steven; Sallis, Geoff; Bertels, Michael; Edgar, Helen E.; Nikolla, Dritan; Buckle, Susanna; Goodwin, Charlotte; Whelan, Allana
Abstract: This paper presents a model of situation awareness (SA) that emphasises that SA is necessarily built using a subset of available information. A technique (Quantitative Analysis of Situation Awareness – QASA), based around signal detection theory, has been developed from this model that provides separate measures of actual SA (ASA) and perceived SA (PSA), together with a feature unique to QASA, a measure of bias (information acceptance). These measures allow the exploration of the relationship between actual SA, perceived SA and information acceptance. QASA can also be used for the measurement of dynamic ASA, PSA and bias. Example studies are presented and full details of the implementation of the QASA technique are provided. Practitioner Summary: This paper presents a new model of situation awareness (SA) together with an associated tool (Quantitative Analysis of Situation Awareness – QASA) that employs signal detection theory to measure several aspects of SA, including actual and perceived SA and information acceptance. Full details are given of the implementation of the tool.